Patogenesitas Virus Gumboro Isolat Lokal pada Ayam Pedaging - Wahyuwardani, Sutiastuti; Agungpriyono, Dewi Ratih; Parede, Lies; Manalu, Wasmen (Jurnal Veteriner; Vol 12 No 4 (2011), 2012)
Study of the pathogenicity of gumboro virus (very virulent Infectious Bursal Disease virus, vvIBDV) oflocal isolates was performed in broilers. The chickens were grouped into four: i) infected with vvIBDV; ii)vaccinated with commercial vaccine + challenge with vvIBDV; iii) vaccinated using locally produced vaccine+ challenged with vvIBDV; and iv) control group (unvaccinated animals). Pathogenecity was analyzedbased on the sequence of infection; the distribution and degree of gross pathology and histopathologylesions on bursa Fabricius, spleen and thymus in relation to the presence of the antigen (IBDV Ag) whichwas detected using immunohistochemistry technique. During the acute phase (1-3 days following theexperimental infection) hyperemia and exudation on the bursa Fabricius were observed in the infectedgroup and the two vaccinated-challenged groups. Similarly, hyperemia was also observed on the spleenand thymus. Whilst during the chronic stages (at 7 and 14 days following the experimental infection) thebursa showed atrophy. Upon histological examination, the bursa showed interstitial edema, hemorrhage,infiltration of heterophyl cells and fibroblast hyperplasia. The bursa lymphoid follicles were depleted dueto cells necrosis and apoptosis. Plica epithelial layer was wrinkled and the Goblet cells metaplasia formedhyper plastic cysts. In the spleen and thymus severe reticulo endothelial cells proliferation was observedduring the acute stage and tended to decline during the chronic stage. During the acute and chronic stagescells containing IBDV Ag were detected in the bursa Fabricius, distributed within the mantle zone andgerminal center of lymphoid follicles in the two vaccinated-challenge groups. Whereas in the infectedgroup, the IBDV antigen were detected up to 7 days post the infection. Nevertheless, neither IBDV antigenwas detected in the spleen nor in the thymus in all the experimental groups. The results of this studyclearly explained the ferocity of vvIBDV of local isolates.
Keywords: pathogenicity, IBD virus, immunohistochemistry, bursa Fabricius, spleen, thymus